Oxidative Stress And Redox-Based Interventions In Chronic Diseases: A Systematic Review - astiah, andi asda (Journal of health research and technology, 2025)
Background:Oxidative stress, characterized by an imbalance between reactive oxygen species (ROS) production and antioxidant defense systems, has emerged as a critical factor in the pathogenesis of various chronic diseases. Understanding its mechanisms and therapeutic implications is essential for developing effective interventions. Objective:This review aims to evaluate the role of oxidative stress in chronic diseases and to analyze the efficacy of pharmacological interventions with antioxidant or pro-oxidant properties across cardiovascular, metabolic, neurodegenerative, and oncological disorders. Methods:A systematic search was conducted across PubMed, Scopus, and Web of Science for articles published between January 2000 and December 2024. Inclusion criteria encompassed original studies (RCTs, observational, and preclinical) examining oxidative stress biomarkers and therapeutic outcomes. Quality assessment employed validated tools including the Cochrane Risk of Bias Tool, Newcastle-Ottawa Scale, and AMSTAR-2. A narrative synthesis approach was used due to heterogeneity in study designs. Results:Malondialdehyde (MDA) and 8-hydroxy-2'-deoxyguanosine (8-OHdG) were the most consistently elevated markers across diseases such as type 2 diabetes mellitus, cardiovascular disease, Parkinson’s disease, COPD, psoriasis, and chronic kidney disease. Antioxidant enzymes—superoxide dismutase (SOD), catalase (CAT), and glutathione (GSH)—were frequently reduced, indicating compromised redox defense. MDA and SOD levels were responsive to lifestyle or pharmacological interventions, highlighting their potential for therapeutic monitoring. Heterogeneity in biomarker assessment methods limited cross-study comparisons. Conclusion:Oxidative stress biomarkers demonstrate consistent alterations across chronic diseases, suggesting their utility in disease monitoring and risk stratification. MDA, 8-OHdG, SOD, and CAT are among the most clinically informative markers. Standardized measurement protocols are essential to improve their translational value in redox-based diagnostics and therapeutic evaluation